A resilient approach to modelling the supply and demand of platelets in the United Kingdom blood supply chain. Issue 2 (3rd April 2021) - Ejohwomu, O.A; Too, J; Edwards, D.J
ABSTRACT: The short shelf-life of platelets together with their stochastic demand and variable supply create problematic decision making for inventory managers who seek to maintain optimal stock levels. This paper develops a novel simulation model that acts as a decision support tool for identifying optimal stock levels to guarantee the availability of stock and, eliminate wastage and outages within the platelet supply chain. A multi-method approach is delineated upon that combines agent-based and discrete event modelling built on Anylogic software using data collected from typical UK Stock Holding Units (SHUs). The model simulates the demand and supply of 24 different platelet types and recommends the appropriate stock level at SHUs. Adopting these stock levels guarantees stock availability and improves performance at the SHU by reducing wastage by 78%. This research not only represents the first attempt to fully understand the UK platelet supply chain but also presents an advanced simulation model that adopts a 'pull' system of platelet inventory management. Further, the concept of resilience is integrated into the design of the solution methodology by testing the model's behaviour on unexpected disruptions in the supply chain.